2013
DOI: 10.1111/hsc.12062
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on barriers to employment for job seekers with mental illness and additional substance-use problems

Abstract: This paper examines the barriers to employment faced by job seekers (JS) with mental illness and additional substance-use issues. Semi-structured interviews concerning barriers to employment for JS with mental illness and substance-use problems and strategies to improve employment outcomes were conducted with stakeholders associated with an employment service provider specialising in mental illness (n = 17). Stakeholders were JS, family members who provide significant support to JS [support persons (SP)] and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…Participants were aware that they could be stigmatized or judged by the dental team, including the receptionist, dental assistant and dental practitioner. This finding is not surprising in a sense that people living with mental illness often do not tell employers and colleagues about their mental illness for the same reasons . Similarly, some participants advised that they would not disclose information about their medications to the dental practitioner, as it would identify their mental illness and therefore may cause stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were aware that they could be stigmatized or judged by the dental team, including the receptionist, dental assistant and dental practitioner. This finding is not surprising in a sense that people living with mental illness often do not tell employers and colleagues about their mental illness for the same reasons . Similarly, some participants advised that they would not disclose information about their medications to the dental practitioner, as it would identify their mental illness and therefore may cause stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Because no current measures were designed to systematically assess barriers and facilitators to work functioning in Veterans with mental illness, the survey was developed by study investigators based on key factors that have been identified by prior literature examining competitive employment in community samples of people with mental illness [12,13,[19][20][21]26]. Existing measures, including a barriers checklist used with non-Veterans [6] and a Likertstyle survey examining work barriers [12] also influenced the design of the current survey.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, qualitative interviews with consumers add to our understanding in this area, and highlight job related themes contributing to work success, such as interest in the job, challenging job tasks, work confidence, and supportive supervisor and co-worker relationships [23]. Lastly, recent research has shed light on additional elements, such as the role of specific contextual and system-level factors [20].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of stigmatisation is seen to hinder integration in many ways (Prince & Prince , Farone , Harris et al . ). For example, internalised stigma correlates significantly with reduced activity, suggesting that changing self‐stigmatising beliefs can act as an aid to integration (Moriarty et al .…”
Section: Introductionmentioning
confidence: 97%